1994
DOI: 10.1007/bf01426074
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and alignment in charge exchange processes involving sodium atoms studied by semi-classical molecular theory

Abstract: Abstract. The semi-classical molecular model is applied to study the charge exchange processes in the H +-Na 3 p and Li+-Na 3p systems in the keV energy range. The dependence of the charge exchange on the orientation and the alignment of the initial or final state is obtained for the transition probabilities and for the differential cross sections. The 14 state present model for the H+-Na system is in good agreement with the experimental differential cross sections. The alignment is explained by orientation oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…In their experimental study of charge transfer from an initially oriented Na * (3p −1 ) state, Richter et al [2] observe left-right asymmetries (or Φ = 0/Φ = π asymmetries) in the Na * (3p −1 ) → H * (n = 2) DCS. These asymmetries, due to the asymmetry of the 3p −1 initial state, are also predicted theoretically by Dubois et al [6] and Courbin et al [16] using semiclassical methods. Here we examine the CTMC deflection angle for each trajectory as a function of the impact parameter and define the DCS for each channel considered (see Sect.…”
Section: Proton Velocity Perpendicular To the Oz Axissupporting
confidence: 78%
See 2 more Smart Citations
“…In their experimental study of charge transfer from an initially oriented Na * (3p −1 ) state, Richter et al [2] observe left-right asymmetries (or Φ = 0/Φ = π asymmetries) in the Na * (3p −1 ) → H * (n = 2) DCS. These asymmetries, due to the asymmetry of the 3p −1 initial state, are also predicted theoretically by Dubois et al [6] and Courbin et al [16] using semiclassical methods. Here we examine the CTMC deflection angle for each trajectory as a function of the impact parameter and define the DCS for each channel considered (see Sect.…”
Section: Proton Velocity Perpendicular To the Oz Axissupporting
confidence: 78%
“…The preferred p −1 orientation in the final state can be explained by invoking the inverse collision Na + + H * (2p): the dominance of the p −1 → p −1 probability allows us to assert that the velocity matching argument applies to this quasi-resonant reaction in the velocity range presently studied. However, although it seems to allow a very simple interpretation of charge transfer mechanism involving oriented states, this criterion is not valid at lower collision velocity, as Courbin et al [16] have shown in the non-resonant Li + −Na * (3p) case.…”
Section: Proton Velocity Perpendicular To the Oz Axismentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the motion of the valence electron is calculated assuming single particle motion around a frozen core. In the first calculation, the model Klapisch potential is employed for this purpose [7,8]:…”
mentioning
confidence: 99%
“…For singly and doubly charged projectiles also semiclassical closecoupling methods succesfully predicted experimental results (e.g. Gieler et al 1993a, Dubois et al 1993, Courbin et al 1994, Rod and Nielsen 1995. With highly charged ions at present the use of this method is prohibited due to practical limits imposed on the basis set size.…”
Section: Introductionmentioning
confidence: 61%